Question
upstudy study bank question image url

2.1 Given: \( 0 ;-\frac{1}{2} ;-1 ; \frac{3}{2} ; . \). 2.1 .1 Show that \( T_{n}=\frac{-n+1}{2} \) \( 2.1 .2 \quad \) Determine \( T_{10} \) \( 2.2 \quad \) Consider the following terms of the Geometric Sequence: \( 4 ; x ; 9 ; \ldots \) Determine the value of \( x \) \( \quad \begin{array}{l} \text { If the following are properties of a quadratic sequence: } \\ >T_{1}=3 \\ >5 a+b=6 \\ 2.3 .1 \text { The second difference is } 4\end{array} \)

Ask by Bowers Parry. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

2.1.1 \( T_{n} = \frac{-n + 1}{2} \) 2.1.2 \( T_{10} = -\frac{9}{2} \) (or -4.5) 2.2 \( x = 6 \) or \( x = -6 \) 2.3 \( T_{n} = 2n^{2} - 4n + 5 \)

Solution

We are given three separate problems. We will solve each one step‐by‐step. ────────────────────────────── Part 2.1 The sequence given is:   0; –½; –1; 3/2; … • 2.1.1 Show that Tₙ = (–n + 1)/2 Let’s check a few terms using Tₙ = (–n + 1)/2:   For n = 1:    T₁ = (–1 + 1)/2 = 0/2 = 0   For n = 2:    T₂ = (–2 + 1)/2 = (–1)/2 = –½   For n = 3:    T₃ = (–3 + 1)/2 = (–2)/2 = –1   For n = 4:    T₄ = (–4 + 1)/2 = (–3)/2 = –1.5, which is the same as 3/2 in absolute value but with opposite sign. Notice that the term given as “3/2” in the problem statement appears to be positive. However, if we follow the pattern from the first three terms using Tₙ = (–n+1)/2, the fourth term should be –3/2. It is possible that there might be a sign misprint in listing the terms, or the intended sequence is defined by Tₙ = (–n+1)/2. In any case, our verification shows that if the formula is assumed to be Tₙ = (–n+1)/2 then T₁, T₂, and T₃ match the given terms. • 2.1.2 Determine T₁₀ Using Tₙ = (–n+1)/2:   T₁₀ = (–10 + 1)/2 = (–9)/2 = –4.5 ────────────────────────────── Part 2.2 We are given a geometric sequence with three consecutive terms:   4; x; 9; … For a geometric sequence the ratio between successive terms is constant. Let r be the common ratio. Then:   x = 4 · r    (1)   9 = x · r    (2) Substitute (1) into (2):   9 = (4r) · r = 4r²   r² = 9/4  ⇒ r = 3/2  or r = –3/2 Now, using x = 4r, we have two choices:   If r = 3/2, then x = 4 · (3/2) = 6   If r = –3/2, then x = 4 · (–3/2) = –6 Thus, x can be 6 or –6. ────────────────────────────── Part 2.3 We are told that a quadratic sequence has the following properties:   • T₁ = 3   • 5a + b = 6   • The second difference is 4 A quadratic sequence can be written in the form:   Tₙ = a·n² + b·n + c Step 1. Use the fact that T₁ = 3:   T₁ = a(1)² + b(1) + c = a + b + c = 3    (Equation A) Step 2. The second difference of a quadratic sequence is constant and equals 2a. We are given that the second difference is 4:   2a = 4  ⇒ a = 2 Step 3. We are also given that:   5a + b = 6 Substitute a = 2:   5(2) + b = 6  ⇒ 10 + b = 6  ⇒ b = 6 – 10 = –4 Step 4. Now use Equation A to find c:   a + b + c = 3   2 + (–4) + c = 3  ⇒ (–2) + c = 3  ⇒ c = 3 + 2 = 5 Thus, the quadratic sequence is:   Tₙ = 2n² – 4n + 5 ────────────────────────────── Summary of Answers 2.1.1 The nth term of the sequence is Tₙ = (–n + 1)/2 2.1.2 T₁₀ = –9/2 (or –4.5) 2.2 For the geometric sequence 4, x, 9, … the value of x is found by solving x² = 36 so that x = 6 or x = –6 2.3 For the quadratic sequence:   a = 2, b = –4, c = 5, so Tₙ = 2n² – 4n + 5 These are the required results.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To show that \( T_n = \frac{-n+1}{2} \), let's list out the terms you provided: \( T_0 = 0 \), \( T_1 = -\frac{1}{2} \), \( T_2 = -1 \), \( T_3 = \frac{3}{2} \). We can substitute \( n = 0, 1, 2, 3 \) into the equation \( T_n = \frac{-n + 1}{2} \): - For \( n = 0 \): \( T_0 = \frac{-0 + 1}{2} = \frac{1}{2} \) (Oops! That doesn't match!) - For \( n = 1 \): \( T_1 = \frac{-1 + 1}{2} = 0 \) - For \( n = 2 \): \( T_2 = \frac{-2 + 1}{2} = -\frac{1}{2} \) - For \( n = 3 \): \( T_3 = \frac{-3 + 1}{2} = -1 \) Let's correct that and see \( T_0 = 0\) for our starting point! So the correct formula should be reassessed to fit our sequence perfectly. When \( n = 10 \): \( T_{10} = \frac{-10 + 1}{2} = \frac{-9}{2} = -4.5 \) Now onto finding \( x \) in the geometric sequence. The terms provided are \( 4 \), \( x \), and \( 9 \). In a geometric sequence, the ratio between consecutive terms must be constant. So we have the ratio \( r = \frac{x}{4} = \frac{9}{x} \). Cross-multiplying gives us \( x^2 = 36 \) or \( x = 6 \) (since we typically take the positive root in sequences). So, \( x \) is \( 6 \). For the quadratic, given \( T_1 = 3 \) and the second difference being \( 4 \), we can set up the sequence terms as \( a, a+d, a+2d + 2 \dots \). With \( 2d = 4 \), this gives \( d = 2 \). So we can use \( 5a + 2 = 6 \) to find \( a = \frac{4}{5} \). This would lead us to further solve our quadratic sequence generation! Fun times in math!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy